Prevalence and Behavior of Nutrition Aware Families Related with the Incidence of Stunting in Todller - Siswanto, Gytta Affrilia; Kamila, Lia (Jurnal Kesehatan Metro Sai Wawai, 2023)
Introduction: Although the Government of Indonesia has implemented behavior of nutrition-aware family programs for a long time. However, it is still the most dominant factor in stunting cases in toddlers. Purpose: To evaluate the effect of Nutrition-aware family behavior on the incidence of stunting in toddlers aged 24-59 months in the working area of Citeureup Community Health Center, North Cimahi District, Cimahi City, Indonesia. Methods: A cross-sectionalÂ study was chosen as the study design with a sample of 76 children aged 24-59. Samples were selected using the cluster random sampling technique. The questionnaire is a research instrument to obtain data on five indicators of nutrition-aware behavior, while the book on maternal and child health is to obtain stunting data. The data were analyzed using the chi-square test. Results: Of the children aged 24-59 months who were stuntedÂ  (14.5%), nearly half did not belong to Nutrition-aware families (36.8%). The study found a relationship between the behavior of nutrition-aware families and the incidence of stunting in toddlers (p-value 0.000; OR 3,824; CI 95%: 2.541-5.753). Conclusion: Behavior of nutrition-aware family programs has not been able to reduce the incidence of stunting in toddlers. The results of this study provide information for consideration in planning intervention strategies to reduce stunting through increasing the role of nutrition-conscious families.Latar Belakang: Walaupun program perilaku keluarga sadar gizi telah diimplementasikan oleh Pemerintah Indonesia sejak lama. Namun, Ia masih sebagai faktor paling dominan terhadap terjadinya kasus stunting pada anak. Tujuan: Untuk mengevaluasi efek perilaku keluarga sadar gizi terhadap kejadian stunting pada anak usia 24-59 bulan di wilayah kerja Pusat Kesehatan Masyarakat Citeureup Kecamatan Cimahi Utara, Kota Cimahi, Indonesia. Metode: Cross-sectional study dipilih sebagai desain penelitian dan melibatkan 76 anak berusia 24-59 bulan sebagai sampel. Sampel diseleksi menggunakan teknik cluster random sampling. Kuesioner sebagai instrumen penelitian untuk memperoleh data lima indikator perilaku sadar gizi serta buku Kesehatan ibu dan anak untuk memperoleh data stunting. Data dianalisis menggunakan uji chi-square. Hasil: Sebagian anak yang mengalami stunting (14,5%), hampir setengahnya tidak termasuk keluarga sadar gizi (36,8%). Studi ini menemukan terdapat hubungan perilaku keluarga sadar gizi dengan kejadian stunting pada anak (p-value 0,001; OR 3,824; CI 95%: 2,541-5,753). Simpulan: Program keluarga sadar gizi belum mampu menurunkan kejadian stunting pada balita. Hasil studi ini memberikan informasi untuk pertimbangan dalam membuat perencanaan strategi intervensi penurunan stunting melalui peningkatan peran keluarga sadar gizi.